The relationship of alanine aminotransferase to metabolic syndrome in a Korean population - Lee, Seok-Hoon; Cho, Doo-Yeoun; Joo, Nam-Seok; Kim, Kwang-Min; Kim, Kyu-Nam (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Although associations between serum alanine aminotransferase and metabolic syndrome are well-recognized in Western countries, only a limited number of prospective studies have been performed in Asian populations. The aim of the study was to cross-sectionally and longitudinally examine whether serum alanine aminotransferase levels are associated with metabolic syndrome and its associated components in a Korean population. Materials and Methods: A total of 31,832 subjects who received health screenings were included in cross-sectional analyses; a subgroup of 4.070 subjects without metabolic syndrome at baseline was included in the longitudinal analyses. The metabolic syndrome definition was based on the National Cholesterol Education Program Third Adult Treatment Panel criteria with modification on waist circumference cut-off to be more appropriate for an Asian population. Results: In the cross-sectional analyses, serum alanine aminotransferase is positively associated with metabolic syndrome and its components. In the longitudinal analyses, the prevalence of metabolic syndrome increased across serum alanine aminotransferase quartiles in a dose-dependent manner after extensive adjustments (hazard ratios were 1.000, 1.609, 2.601, and 3.015 for quartiles, 1 through quartile 4; P for trend Conclusion: Our study confirmed a positive association between components of metabolic syndrome and elevated serum alanine aminotransferase in a Korean population. Cite this article as: Lee SH, Cho DY, Joo NS, Kim KM, Kim KN. The relationship of alanine aminotransferase to metabolic syndrome in a Korean population. Turk J Gastroenterol 2018; 29: 50-7.